Changes in pulmonary artery pressure before and after left ventricular assist device implantation in patients utilizing remote haemodynamic monitoring. (23rd October 2018) - Kilic, Ahmet; Katz, Jason N.; Joseph, Susan M.; Brisco‐Bacik, Meredith A.; Uriel, Nir; Lima, Brian; Agarwal, Rahul; Bharmi, Rupinder; Farrar, David J.; Lee, Sangjin; ,
Abstract: Aims: The time course of changes in pulmonary artery (PA) pressure due to left ventricular assist devices (LVADs) is not well understood. Here, we describe longitudinal haemodynamic trends during the peri‐LVAD implantation period in patients previously implanted with a remote monitoring PA pressure sensor. Methods and results: We retrospectively studied PA pressure trends in patients implanted with CardioMEMS™ PA pressure sensor between October 2007 and March 2017 who subsequently had an LVAD procedure. Data are presented as mean ± standard deviation, and P ‐values are calculated using standard t ‐test with equal variance. Among 436 patients in cohort, 108 (age 58 ± 11 years, 82% male) received an LVAD and 328 (age 60 ± 13 years, 70% male) did not. The mean PA pressure at sensor implant was higher by 29% ( P < 0.001) among patients who later received LVAD. Mean PA pressure 6 months prior to LVAD implant was 35.5 ± 8.5 mmHg, increasing to 39.4 ± 9.9 mmHg ( P = 0.04) at 4 weeks before LVAD, and then decreasing 27% to 28.8 ± 8.4 mmHg ( P < 0.001) at 3 months post‐implant and stabilizing at 31.0 ± 9.4 mmHg at 1 year. Conclusions: Patients who later receive LVADs have higher PA pressures at sensor implant and show a further increase leading up to LVAD implantation. There is a significant reduction of PA pressures post‐LVAD implantation that persists long term. PA pressure monitoring may aid in the clinical decision making of timing for LVAD implantation and in management of LVAD patients.